When do general practitioners request urine specimens for microbiology analysis? The applicability of antibiotic resistance surveillance based on routinely collected data. - Hillier, S; Bell, J; Heginbothom, M; Roberts, Z; Dunstan, F; Howard, A; Mason, B; Butler, C (2006)
OBJECTIVES: We do not know how representative reported levels of resistance to antibiotics in urinary tract infections (UTIs) are as there is wide variation in the rate of urine specimens submitted to microbiology laboratories by general practices. We used a questionnaire to investigate variation in sampling for patients with suspected UTI to explore any systematic bias that may influence interpretation of surveillance data based on routine data. METHODS: We sent a questionnaire to a stratified random sample of general practitioners (GPs) in Wales for self-completion. The GPs were presented with six clinical scenarios and asked about their proposed clinical management. RESULTS: We found that nearly all of the GPs indicated they would request a specimen for scenarios representing a probable UTI in a female child and a probable asymptomatic UTI in pregnancy. There was some variation between the GPs about sampling in a situation of treatment failure in an older woman and recurrent UTI in a male diabetic, with 90% and 81%, respectively, indicating they would request a specimen for these scenarios. The greatest variation was in relation to scenarios concerning the management of a probable uncomplicated UTI, and early patient symptoms with pressure to prescribe, with 56% and 33% of GPs, respectively, indicating they would request a urine specimen for laboratory analysis. CONCLUSIONS: In the light of this reported sampling behaviour, it is likely that there is a systematic bias in surveillance data based on routinely collected data, with samples from cases of uncomplicated UTI being under represented, potentially leading to an overestimation of true resistance rates.